Analysis of The Performance on Wheel Rim Towards Impact Test: Wheel Rim Impact - Jabidi, Nurlaily Fatin; Rahmah Mahmudin (Progress in Engineering Application and Technology, 2021)
The wheel rim is one of the vehicle’s most critical components because it protects the collision driver and passengers. There are several wheel tests available in designing rim to fulfill the safety requirements and standards. Before testing the wheel rim, knowing the materials is vital because selecting materials helps to lightweight rim contributes to the vehicle’s weight reduction, eventually reducing fuel consumption other than safe to use. The study aims to perform the impact wheel rim using three different materials, namely Aluminum A356.2, Magnesium AM60B, and Titanium TC4. All the wheel rim impact materials will be analyzed using the ANSYS Additive R3 2019 software’s numerical method. In this paper, the wheel rim simulates 13 degrees, and then the striker taps the wheel rim at a specific height. The striker is set to step down with a drop height of 230mm and 400mm. All these analyses using explicit dynamic finite element methods. This study’s Magnesium AM60B findings have the highest deformation and the lowest equivalent stress, followed by Aluminum A356.2 and Titanium TC4. In order to analyze the result, obtain, and recommend an optimal material based on the impact test. The analysis results have presented the deformation, stress, and strain during the impact of the wheel rim test.